Improvement by imagining actions: Bimanual transfer effects after action imagery practice in a sequential reaction time task - Stephan F. Dahm; Sandra Sülzenbrück; Martina Rieger (Acta Psychologica)
Action-imagery-practice refers to the repetitive use of action imagery to improve subsequent performance leading to partially different representation types than action-execution-practice (AEP). This study explored the representation types in kinesthetic action-imagery-practice (K-AIP) and visual action-imagery-practice (V-AIP) in a serial reaction time task using the crossed hand transfer paradigm. 169 participants (age M ± SD = 25.2 ± 3.9) were randomly assigned to AEP, K-AIP, V-AIP, or control-practice (CP), practicing with uncrossed hands on ten consecutive days. Tests involved the same sequence, a mirror sequence, a shifted sequence, and a shifted mirror sequence, each with uncrossed and crossed hands. With crossed hands, sequence-specific transfer effects indicated only little evidence for effector-independent representations in late stages of learning in AEP and V-AIP. Performance in the same sequence with uncrossed hands indicated the acquisition of stimulus-response location associated effector-dependent sequence-specific representations in AEP, K-AIP and V-AIP, but not in CP. These visual-spatial effector-dependent representations were stronger after AEP than after AIP. Overall, no important differences between both AIP groups were observed, and both groups reported similar focus on kinesthesis and vision, suggesting that irrespective of the instructions, rather than focusing on one single modality, AIP always involves a combination of both modalities - vision and kinesthesis - that promote motor learning.